THE IMPORTANCE OF STUDYING AND DEVELOPING COMPETENCE IN FUTURE HISTORY TEACHERS - Boltaeva Moxichekhra (International Scientific and Current Research Conferences, 2022)
In our time, the formation of universal competence among future teachers of history is very important, as it is necessary to improve the system of historical education. The most effective way to form knowledge about historical ideals and an objective worldview in future history teachers is to organize the pedagogical process based on an integrated approach. To this end, it is necessary to consider the current state of the system for training future teachers of history.